Sustainable lightweight self-compacting concrete with coal bottom ash as aggregate and cement replacement - Ibtissam Boulahya; Abdelkadir Makani; Ahmed Tafraoui (The Journal of Engineering and Exact Sciences)
This study aims to examine the impact of utilizing coal bottom ash (CBA) sourced from an inactive power plant on the fresh and hardened properties of lightweight self-compacting concrete (LWSCC). To evaluate the workability of the LWSCC mixtures, slump flow, L-box, and sieve segregation tests were performed. The mechanical and physical properties were assessed through dry density, compressive strength and ultrasonic pulse velocity (UPV) tests. A total of five concrete mixes were developed: a control mix and four additional mixtures in which natural coarse aggregate was fully substituted with coal bottom ash aggregate (CCBA). Additionally, Portland cement was partially replaced with coal bottom ash powder (CBAP) at levels of 15%, 20%, and 25%. The results indicated that the use of CBA as a coarse aggregate enhanced the workability of LWSCC, though workability decreased as the proportion of CBAP increased. Nonetheless, the workability of all mixes remained compliant with the standards specified by the French Association of Civil Engineering (AFGC). Minimal variations in dry density and compressive strength were observed with the incorporation of CBA; however, these values remained within the acceptable limits for structural lightweight concrete. Furthermore, the UPV test demonstrated favorable durability for all LWSCC mixtures. Strong linear correlations were identified among the various measured properties, reinforcing the conclusion that CBA serves as an effective replacement for natural coarse aggregate. Moreover, the use of 15% CBAP as a partial substitute for Portland cement proved to be a feasible option for producing sustainable LWSCC.